An Investigation into politeness strategies used in conversation in the course book Let s talk 1,2 and 3 - Bùi Thị Anh Thư (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
English speakers who are using English as a second language need to learn how to use English properly to deliver their ideas but also they need to be familiar with how native English speakers communicate politely in each circumstance. In order to avoid embarrassing other people or making people feel uncomfortable, it is necessary to be aware of politeness strategies. Applying the politeness theory of Brown, P. & Levinson, S. C (1978), the study investigates politeness strategies used in analyzing conversations of the popular course books – Let’s Talk 1, 2 and 3. The study results show that positive politeness strategies are preferred in almost all the speech acts. The study emphasizes the significance of politeness strategies in communication, classifies politeness strategies employed in conversations in the listening sections of the course books Let’s Talk 1, 2 and 3 and provides implications in teaching politeness strategies in English communication.